The Effect of Temperature and Heating Time of Roselle Extract (Hibiscus Sabdariffa L) Powder Solution on Growth Inhibition of Staphylococcus aureus ATCC 25923 - Hana Sofiana Maghfira; Isnaeni Isnaeni; Asri Darmawati (Universitas Airlangga, 2021)
The main ingredients of roselle (Hibiscus sabdariffa L.) which have antioxidant and antibacterial effect were anthocyanins, and flavonoids. Flavonoid compounds were unstable at high temperatures. Meanwhile, the processing of roselle extract powder into ready-to drink or food preparations generally requires the thermal processes. The aims of this study were to determine the effect of temperature and heating time of roselle extract powder solution on the inhibition of microbial growth of Staphylococcus aureus ATCC 25923. The method of this study uses a ready-to- process roselle powder extract sample. The roselle extract powder solution in a screw cap tube was heated at a temperature of 40°C, 50°C, 60°C, 70°C, 80°C, and 90°C on a waterbath, with heating times at each temperature were 15 minutes and 30 minutes. Anti bacterial activity of the sample solution was measured based on the ability to inhibit the growth of Staphylococcus aureus ATCC 25923 by the agar-well diffusion method. The inhibition zone of the sample was measured by caliper. The result of this study showed that inhibition zones caused by the sample that had been heated at those temperature for 15 minutes were 9.55±0.70 mm, 9.53 ±0.04 mm, 9.70±0.14 mm, 9.68±0.24 mm, 10.10±0.14 mm, and 10.25±0.21 mm. Meanwhile, after heating for 30 minutes the inhibition zones were 10.08±0.25 mm, 10.20±0.28 mm, 10.43±0.18 mm, 10.08±0.18 mm, 10.78±0.04 mm, 9.70±0.14 mm. Two ways statistical test ANOVA Randomized Control Block Design with 95% confidence level was used to prove that there was a significant difference berween the mean inhibition zones of each sample. The conclution of this research was, the temperature in the range of 40 -90 oC has no effect on the anti-bacterial activity of the sample. However, the heating time of the sample affected the antibacterial activity of the roselle extract powder solution against Staphylococcus aureus ATCC 25923.